Determination of intracellular cytokines produced by Th1 and Th2 cells using flow cytometry in patients with brucellosis - Akbulut, HH; Kilic, SS; Bulut, V; Ozden, M (Elsevier Science Bv, 2005)
The aim of the study was to evaluate intracellular interferon-gamma (IFN-gamma), and interleukin-4 (IL-4) levels in pre- and post-treatment periods of brucellosis patients and to determine the relationship between these parameters and patients' clinical findings. Twenty-five patients diagnosed as brucellosis and 11 aged-matched healthy volunteers were included in the study. CD3(+)CD4(+) T lymphocytes levels were significantly lower in patients with brucellosis as compared to the control group. CD3(+)CD8(+) T lymphocytes and CD3(+)IFN-gamma(+) levels were increased in brucellosis patients compared with the control group. CD4(+)IFN-gamma(+) and CD4(+)IL-4(+) levels were no different between patients and healthy individuals. CD3(+)IL-4(+) levels decreased in patients compared with healthy controls. Pre-treatment CD3(+)IFN-gamma(+) levels dramatically increased in patients responsive to management compared with the unresponsive ones. In responsive cases, CD3(+)IFN-gamma(+) levels decreased statistically after the treatment while in unresponsive cases no meaningful change was observed with respect to treatment. Adding IFN-gamma to the treatment for improving the depleted levels of IFN-gamma can be beneficial in patients with brucellosis who shows a tendency to chronicity or patients who do not respond to the treatment. (c) 2005 Federation of European Microbiological Societies. Published by Elsevier B.V. All rights reserved.
Keywords: brucellosis; intracellular cytokine; interferon-gamma; IL-4